(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the foreign language teacher recommends types of extracurricular activities to students, prepares materials, and analyzes the methods of conducting them. They coordinates some events at the school level and mobilizes students according to the types of work, divides them into groups and assigns tasks, supervises the execution of assigned tasks. We will consider the extracurricular activities that students participate in one by one.